Effect of altitude on mortality of end-stage renal disease patients on hemodialysis in Peru - Bravo-Jaimes, Katia (2021)
Background. In Latin America, the prevalence of end-stage kidney disease (ESKD) has risen tremendously during the last decade. Previous studies have suggested that receiving dialysis at high altitude confers mortality benefits; however, this effect has not been demonstrated at >2000 m above sea level (masl) or in developing countries. Methods. This historical cohort study analyzed medical records from six Peruvian hemodialysis (HD) centers located at altitudes ranging from 44 to 3827 masl. Adult ESKD patients who started maintenance HD between 2000 and 2010 were included. Patients were classified into two strata based on the elevation above sea level of their city of residence: low altitude (<2000 masl) and high altitude (2000 masl). Death from any cause was collected from national registries and Cox proportional hazards models were built. Results. A total of 720 patients were enrolled and 163 (22.6%) resided at high altitude. The low-altitude group was significantly younger, more likely to have diabetes or glomerulonephritis as the cause of ESKD and higher hemoglobin. The all-cause mortality rate was 84.3 per 1000 person-years. In the unadjusted Cox model, no mortality difference was found between the high- and low-altitude groups fhazard ratio [HR] 1.20 [95% confidence interval (CI) 0.89–1.62]g. After multivariable adjustment, receiving HD at high altitude was not significantly associated with higher mortality, but those with diabetes as the cause of ESKD had significantly higher mortality [HR 2.50 (95% CI 1.36–4.59)]. Conclusions. In Peru, patients receiving HD at high altitudes do not have mortality benefits.